The Role of Pesantren in Fighting Religious Radicalism in West Sumatra - Muhammad Ridha; Zainal Zainal; Nofri Andy.N (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article aims to examine the role of pesantren (Indonesian Islamic boarding schools) in West Sumatra in countering religious radicalism. The two pesantren used as case studies are the Pesantren Sumatera Thawalib Parabek Banuhampu and the Perguruan Islam Darul Muwahhidin Panyalaian West Sumatra. This issue is critical to reveal because radicalism targets adults and Islamic boarding school students who are in the process of deepening and understanding religious knowledge. The existence of pesantren in educating students and instilling friendly Islamic values has become a little disturbed by the issue of radicalism which has spread to pesantren. The method used in this study is a qualitative method with a historical approach. The reality that occurs in the pesantren is revealed along with the history and background of the establishment of the pesantren. The results of this study indicate that the learning system in pesantren can counteract radicalism through several things, including strengthening the capacity of students, reviewing the curriculum, enlightening teachers and employees regarding radicalism, and having a friendly and tolerant environment for students.Artikel ini bertujuan untuk mengkaji peran pesantren di Sumatra Barat dalam menangkal paham radikalisme agama. Dua pesantren yang dijadikan studi kasus adalah Pondok Pesantren Sumatra Thawalib Parabek Banuhampu dan Perguruan Islam Darul Muwahhidin Panyalaian Sumatra Barat. Isu ini penting diungkap karena radikalisme ternyata tidak hanya menyasar orang dewasa namun juga santri pesantren yang sedang berproses dalam mendalami dan memahami ilmu agama. Keberadaan pesantren dalam mendidik santri dan menanamkan nilai-nilai Islam yang ramah menjadi sedikit terganggu dengan adanya isu radikalisme telah menjalar ke pesantren. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan historis, realitas yang terjadi di pesantren diungkap bersamaan dengan histori dan latar belakang berdirinya pesantren. Hasil dari penelitian ini menunjukkan bahwa sistem pembelajaran di pesantren dapat menangkal radikalisme melalui beberapa hal, di antaranya: penguatan kapasitas santri, peninjauan kurikulum, pencerahan bagi guru dan pegawai terkait radikalisme dan adanya lingkungan yang ramah dan toleran bagi santri.